La psicología de la adolescencia: algunos aspectos del desarrollo - Monks, Franz J. (1987)
In this article the author presents his point of view about adolescence as an important period in the developmcnt of the individual. He includes general conccpts, an heuristic model and characteristícs that are typical in an adolescents.